A new method for solving arcs of pantograph network based on Newton's iterative method. Issue 1 (1st December 2022) - Liu, Dawei; Wang, Zhe; Gao, Zhiwei; Ye, Zhihong; Wang, Yunfeng; Zuo, Shaoqi
Abstract: It has been verified that the discharge pulse generated by the pantograph-catenary system has the biggest impact on the high-speed EMU as the electromagnetic interference source. But the spectrum obtained from the existing pantograph discharge model does not contain high frequencies and is far from the measurement results. In this paper, a novel scheme based on Newton's method and finite difference time domain (FDTD) algorithm was presented to solve this problem. Firstly, Newton's method was utilized to solve the Habedank model, and the dynamic conductance of the arc was obtained. Then, the equivalent distributed parameter circuit model of the traction power supply system was established, which was solved by the FDTD and state variable method to obtain the time-domain waveform of the arc voltage. The significant features of this scheme are that it can realize the synchronous calculations of the arc dynamic conductance and the voltage responses along the catenary. Through this scheme, a stable arc voltage time domain waveform can be obtained, and the arc voltage spectrum is highly consistent with the test results.